Given differential equation "\\frac{\u2202z}{\u2202x}[1+(\\frac{\u2202z}{\u2202y}) ^2]=\\frac{\u2202z}{\u2202y}(z-a)"
we know that, "p = \\frac{\u2202z}{\u2202x}" and "q = \\frac{\u2202z}{\u2202y}"
Let "u = x + by"
Then "p = \\frac{dz}{du}" and "q = b\\frac{dz}{du}"
Then equation will be
"\\frac{dz}{du}[1 +b^2(\\frac{dz}{du})^2 ] = b(\\frac{dz}{du})(z-a)"
"\\frac{dz}{du} = \\frac{\\sqrt{(bz-ab-1)}}{b}"
Integrating equation,
"\\int\\frac{bdz}{\\sqrt(bz-ab-1)} = \\int du"
"2\\sqrt{(bz-ab-1)} = u + C"
then
"4(bz-ab-1) = (u+C)^2"
putting value of u,
"4(bz-ab-1) = (x+by+C)^2"
which is the required solution.
Comments
Leave a comment